2002
DOI: 10.1001/jama.287.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Dementia Among White and African American Relatives of Patients With Alzheimer Disease

Abstract: First-degree relatives of African Americans with AD have a higher cumulative risk of dementia than do those of whites with AD. However, in this study, the additional risk of dementia conferred by being a first-degree relative, by being female, or by the probability of having an APOE epsilon4 allele appeared similar in African American and white families. These data provide estimates of dementia risk that can be used to offer counseling to family members of patients with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
261
2
6

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 346 publications
(279 citation statements)
references
References 38 publications
(38 reference statements)
10
261
2
6
Order By: Relevance
“…The MIRAGE study is the largest genetic epidemiological study of its kind to date, focusing on both African American and white families. 13,14,65 As a result, it provided a potential basis for clarifying risk profiles for African Americans and risk estimates to FDRs of persons with AD. The study found significantly higher risk for dementia among FDRs of African Americans compared with whites (RR 1.6; 95% CI 1.4 -1.9).…”
Section: The Mirage Studymentioning
confidence: 99%
See 3 more Smart Citations
“…The MIRAGE study is the largest genetic epidemiological study of its kind to date, focusing on both African American and white families. 13,14,65 As a result, it provided a potential basis for clarifying risk profiles for African Americans and risk estimates to FDRs of persons with AD. The study found significantly higher risk for dementia among FDRs of African Americans compared with whites (RR 1.6; 95% CI 1.4 -1.9).…”
Section: The Mirage Studymentioning
confidence: 99%
“…The study also found similar effects of APOE genotype on overall AD risk for African Americans as reported for whites. 13 A comparison of risk through age 85 by self-identified ethnicity and genotype is provided in Table 1.…”
Section: The Mirage Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Risk estimates were formulated using two sources: (1) agespecific incidence curves for first-degree relatives of individuals affected by AD from a genetic epidemiology study of AD families [17][18] ; and (2) odds ratio estimates reported in a metaanalysis encompassing 40 studies worldwide. 19 Bayes' rule was used to stratify risk according to APOE genotype.…”
Section: Risk Estimatesmentioning
confidence: 99%